The Effect of Customer Experience, Service Quality, and Brand Engagement on Brand Perception in the Multimedia Industry: A Case Study of SON Videoworks - Satria Veriansyah Wiguna; Putri Dini Octavia Ardiansyah (International Journal of Entrepreneurship, Business, and Creative Economy, 2025)
This study examines the influence of customer experience, service quality, and brand engagement on brand perception at the multimedia company SON Videoworks. Positive brand perception is the key to fostering customer loyalty and generating recommendations in the competitive creative services industry.This study employs a quantitative approach through a survey of 150 SON Videoworks customers using a Likert-scale questionnaire which was tested for validity and reliability. Data analysis with multiple linear regression reveals that customer experience, service quality, and brand engagement have a significant positive impact on brand perception, both individually and collectively. Customer experience has the strongest influence. The results highlight the importance of delivering a positive and meaningful customer experience, which is supported by dependable service and strong emotional connections with the brand. The study offers strategic insights for SON Videoworks to enhance competitiveness by strengthening brand perception through consistent, high-quality customer interactions.